Depiction of Masculinity in the Advertisement ’PRUFuture Prudential Life Insurance, #SimpleButMeaningful Protecting Families Now and in the Future’ - Aulia Herdani, Diza; Prasetya, Hendri; Setiawati, Titin (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
Traditional masculinity remained deeply embedded in society, associating values such as strength, independence, power, and work primarily with men. This study aimed to examine the portrayal of masculinity in the male lead character of Prudential Indonesia’s advertisement titled "PRUFuture Prudential Life Insurance: #SimpleButMeaningful Protecting Families Now and in the Future." The research employed a qualitative descriptive method, utilizing data collection techniques such as documentation, observation, and interviews with gender observers. The findings revealed that the advertisement depicted six out of seven characteristics of traditional masculinity, including physical appearance, functionality, sexuality, intellect, interpersonal skills, and personal character. These portrayals reinforced conventional gender norms that continued to shape societal expectations of men. Understanding such representations was essential in analyzing the broader impact of advertising on gender perceptions.